Immune contexture of paediatric cancers. (July 2022) - Thakur, Meghna Das; Franz, Carl J.; Brennan, Laura; Brouwer-Visser, Jurriaan; Tam, Rachel; Korski, Konstanty; Koeppen, Hartmut; Ziai, James; Babitzki, Galina; Ranchere-Vince, Dominique; Vasiljevic, Alexandre; Dijoud, Frédérique; et al.
Abstract: Background: The clinical development of immune checkpoint–targeted immunotherapies has been disappointing so far in paediatric solid tumours. However, as opposed to adults, very little is known about the immune contexture of paediatric malignancies. Methods: We investigated by gene expression and immunohistochemistry (IHC) the immune microenvironment of five major paediatric cancers: Ewing sarcoma (ES), osteosarcoma (OS), rhabdomyosarcoma (RMS), medulloblastoma (MB) and neuroblastoma (NB; 20 cases each; n = 100 samples total), and correlated them with overall survival. Results: NB and RMS tumours had high immune cell gene expression values and high T-cell counts but were low for antigen processing cell (APC) genes. OS and ES tumours showed low levels of T-cells but the highest levels of APC genes. OS had the highest levels of macrophages (CSF1R, CD163 and CD68), whereas ES had the lowest. MB appeared as immune deserts. Tregs (FOXP3 staining) were higher in both RMS and OS. Most tumours scored negative for PD-L1 in tumour and immune cells, with only 11 of 100 samples positive for PD-L1 staining. PD-L1 and OX40 levels were generally low across all five indications. Interestingly, NB had comparable levels of CD8 by IHC and by gene expression to adult tumours. However, by gene expression, these tumours were low for T-cell cytotoxic molecules GZMB, GZMA and PRF1. Surprisingly, the lower the level of tumour infiltrative CD8 T-cells, the better the prognosis was in NB, RMS and ES. Gene expression analyses showed that MYCN-amplified NB have higher amounts of immune suppressive cells such as macrophages, myeloid-derived suppressor cells and Tregs, whereas the non-MYCN-amplified tumours were more infiltrated and had higher expression levels of Teff. Conclusions: Our results describe the quality and quantity of immune cells across five major paediatric cancers and provide some key features differentiating these tumours from adult tumour types. These findings explain why anti-PD(L)1 might not have had single agent success in paediatric cancers. These results provides the rationale for the development of biologically stratified and personalised immunotherapy strategies in children with relapsing/refractory cancers. Highlights: The immune contexture of paediatric tumours remains unknown compared with adult cancers. No PD-L1 expression was found on cancer and immune cells of 5 major paediatric cancers. CD163, CSF1R and CD68 myeloid cells were abundant in all tumours except Ewing sarcoma. Some tumours have high levels of infiltrating T-cells but lack efficient activation. Biologically stratified immunotherapy strategies are needed for paediatric oncology.